Maximal and submaximal physiological responses to adaptation to deep water running - Azevedo, L. B.; Lambert, M. I.; Zogaib, P. S.; Barros Neto, T. L. (Journal of Sports Sciences, 2010)
The aim of the study was to compare physiological responses between runners adapted and not adapted to deep water running at maximal intensity and the intensity equivalent to the ventilatory threshold. Seventeen runners, either adapted (n = 10) or not adapted (n = 7) to deep water running, participated in the study. Participants in both groups undertook a maximal treadmill running and deep water running graded exercise test in which cardiorespiratory variables were measured. Interactions between adaptation (adapted vs. non-adapted) and condition (treadmill running vs. deep water running) were analysed. The main effects of adaptation and condition were also analysed in isolation. Runners adapted to deep water running experienced less of a reduction in maximum oxygen consumption ([Vdot]O2max) in deep water running compared with treadmill running than runners not adapted to deep water running. Maximal oxygen consumption, maximal heart rate, maximal ventilation, [Vdot]O2 at the ventilatory threshold, heart rate at the ventilatory threshold, and ventilation at the ventilatory threshold were significantly higher during treadmill than deep water running. Therefore, we conclude that adaptation to deep water running reduces the difference in [Vdot]O2max between the two modalities, possibly due to an increase in muscle recruitment. The results of this study support previous findings of a lower maximal and submaximal physiological response on deep water running for most of the measured parameters.